2007
DOI: 10.1074/jbc.m705719200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Physical Interaction between the Immunoglobulin Heavy Chain Variable Region and the 3′ Regulatory Region

Abstract: B cell-specific expression of immunoglobulin heavy chain (IgH) genes utilizes two cis regulatory regions, the intronic enhancer (E ), located in the J H -C intron, and a complex regulatory region that lies 3 to the IgH gene cluster, 3 RR. We hypothesized that the 3 RR is involved in IgH gene transcription in plasma cells via physical interaction between distal 3 RR enhancers and target V H sequences, with loop formation by intervening DNA. In support of this hypothesis we report sequence data at DNA recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 36 publications
(45 reference statements)
3
71
0
Order By: Relevance
“…The major players in such synapses are the 39 LCR, the intronic enhancer Em, and the V H promoter of the rearranged VDJ exon that are found juxtaposed in resting and activated B cells (31,32). Upon activation, donor and acceptor switch regions might be recruited to the former synapse to be transcribed and recombined in a CSR synaptic holocomplex (32).…”
Section: Discussionmentioning
confidence: 99%
“…The major players in such synapses are the 39 LCR, the intronic enhancer Em, and the V H promoter of the rearranged VDJ exon that are found juxtaposed in resting and activated B cells (31,32). Upon activation, donor and acceptor switch regions might be recruited to the former synapse to be transcribed and recombined in a CSR synaptic holocomplex (32).…”
Section: Discussionmentioning
confidence: 99%
“…Longrange interactions between the two regions of chromatin, through formation of a loop structure, constitute an important mechanism of normal and abnormal gene transcription regulation by the 3 0 RR. Studies have reported interactions between the 3 0 RR, Em and the IgH variable region in normal and lymphomagenetic contexts [19,20,35,36]. Mouse models for oncogene translocations involving the IgH locus effectively produce an insight into the molecular mechanisms of the translocated oncogene deregulation involved in B-cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…If a global IgH transcription defect is observed in activated 3 0 RR-deficient mouse B cells, the persistence of IgM expression and germline transcription suggests that additional elements, such as Em, must cooperate with the 3 0 RR. Chromosome conformation capture experiments suggest the production of unique chromosomal loops in peripheral B cells anchored by Em and 3 0 RR physical interactions [19,20]. In the case of CSR, recruitment and transcription of the switch-acceptor region in close proximity to the switch m donor region (switch--switch synapsis) might be promoted by the 3 0 RR itself [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Although the Ig heavy-and lightchain enhancers contain binding sites for numerous different classes of transcription factors, Ig gene variable region promoters seem to be less complex and predominantly contain a motif termed the octamer element (59-ATGCAAAT-39), which is located 10-25 nucleotides upstream of the TATA box. The canonical octamer or its reverse complement is conserved in all Ig heavy-and light-chain variable region promoters.…”
Section: Introductionmentioning
confidence: 99%